2023
DOI: 10.1186/s12870-023-04162-6
|View full text |Cite
|
Sign up to set email alerts
|

Comparative proteome profiles of Polygonatum cyrtonema Hua rhizomes (Rhizoma Ploygonati) in response to different levels of cadmium stress

Abstract: Background The Polygonatum cyrtonema Hua rhizomes (also known as Rhizoma Polygonati, RP) are consumed for their health benefits. The main source of the RP is wild P. cyrtonema populations in the Hunan province of China. However, the soil Cadmium (Cd) content in Huanan is increasing, thus increasing the risks of Cd accumulation in RP which may end up in the human food chain. To understand the mechanism of Cd accumulation and resistance in P. cyrtonema, we subjected P. cyrtonema plants to four le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 61 publications
0
2
0
Order By: Relevance
“…This inconsistency could potentially arise from variations in the treatments applied, their concentrations, and the plant species under investigation. Studies specifically focusing on the effect of this gene on stress tolerance and secondary metabolite production in C. roseus were lacking, and limited studies were found on other plant species as well [ 81 , [94] , [95] , [96] , [97] , [98] ].…”
Section: Discussionmentioning
confidence: 99%
“…This inconsistency could potentially arise from variations in the treatments applied, their concentrations, and the plant species under investigation. Studies specifically focusing on the effect of this gene on stress tolerance and secondary metabolite production in C. roseus were lacking, and limited studies were found on other plant species as well [ 81 , [94] , [95] , [96] , [97] , [98] ].…”
Section: Discussionmentioning
confidence: 99%
“…In the soil–plant ecosystem, once the Cd levels exceed 8 mg/kg, Cd can inhibit plant growth and cause necrosis by impairing carbon fixation, compromising photosynthetic activity, and generating excess amounts of reactive oxygen species (ROS) that can severely reduce crop yield and quality . As contamination in soil at 12 mg/kg damaged sunflower cell membranes, induced oxidative stresses, and reduced net photosynthetic rates; also, exposure to 80 mg/kg As inhibited the uptake of essential nutrients and reduced crop production in winter wheat .…”
Section: Introductionmentioning
confidence: 99%